Cameroon - Debt Relief Grant under the Enhanced Heavily Indebted Poor Countries (HIPC) Debt Initiative - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The objective of debt relief grant operation was to provide Cameroon the assistance required by IDA under the enhanced HIPC Debt Initiative upon Cameroon reaching the completion point, thus contributing to improving Cameroon's overall debt sustainability and supporting the government's implementation of its poverty reduction strategy through increased spending from the fiscal savings. The policy areas supported by the program are those linked to the conditions for reaching the completion point under the enhanced HIPC debt initiative, namely: (i) preparation of a poverty reduction strategy paper (PRSP), and satisfactory implementation for at least one year; (ii) the maintenance of a stable macroeconomic framework and continued satisfactory performance under the IMF's Poverty Reduction and Growth Facility (PRGF) program; (iii) use of budgetary savings from the interim debt service relief; (iv) the satisfactorily implementation of the structural reforms supported by the Third Structural Adjustment Credit (SAC III) financed by IDA; (v) implementation of governance and anti-corruption measures in the areas of judicial reform, budget execution, procurement reform, and the creation of regulatory agencies; and (vi) implementation of key social reforms, including combating malaria and HIV/AIDS. Some of the lessons are as follows: (i) formulate a realistic timeframe for the government to meet the triggers of the completion point; and (ii) ensure that the government puts in place a strong focal point/unit to coordinate and monitor the implementation of the completion point triggers and facilitate related post completion point actions.